Digital Cultural Heritage – an Overview of the Field (KULT_online, 2021)
The edited volume Digital Cultural Heritage is a collection of thirty contributions dealing with cultural heritage in the digital context. Covering a broad geographical and chronological scope, it presents the reader with an extensive overview of the current work in the field. Some of the topics that were given special attention in the volume are questions of preservation and presentation of (digital) cultural heritage, as well as possibilities for its enrichment with the help of digital tools. While rich in examples, the volume, however, lacks reader guidance and a rounded approach to the topic.